Penguatan Karakter Religius Dan Kreativitas Anak Melalui Permainan Edukatif Pendidikan Jasmani Di Gampong Lambheu Kecamatan Darul Imarah Kabupaten Aceh Besar - Kurniawan, Erizal; Akbar, Aldiansyah; Juwanda , Rawi Juwanda; Syafira, Nada (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2026)
Strengthening religious character and creativity is an essential aspect of elementary school education. This community service research aims to enhance children’s religious character and creativity through educational games based on physical education in Gampong Lambheu, Darul Imarah District, Aceh Besar Regency. The program was conducted over four weeks with two sessions per week, involving 50 children, and integrated interactive religious education with physical activities designed to stimulate creativity and teamwork. The results showed measurable improvements across all aspects, with religious character increasing from 60% to 82% (22%), creativity from 58% to 80% (22%), and social skills from 62% to 85% (23%). In addition, children demonstrated higher participation levels and improved social interaction during the activities. The holistic and collaborative approach, involving families, the community, and local government, proved effective in supporting the sustainability of the program. These findings indicate that educational games based on physical education represent an innovative and effective model for strengthening children’s religious character and creativity within a community-based setting.